Chromosome 17q21.31 duplication syndrome: Description of a new familiar case and further delineation of the clinical spectrum. (January 2016) - Natacci, Federica; Alfei, Enrico; Tararà, Lucia; D'Arrigo, Stefano; Zuffardi, Orsetta; Gentilin, Barbara; Pantaleoni, Chiara
Abstract: Introduction: 17q21.31 microduplication syndrome is a recently described condition associated with a broad clinical spectrum, of which psychomotor delay, behavioral disorders and poor social interaction seem to be the most consistent features. Only seven patients have been reported thus far. All have behavioral disorders reminiscent of the autistic spectrum with intellectual skills ranging from normal to mild intellectual deficiency. Other features are variable with no striking common phenotypic features. Case study: Here we describe the segregation of 17q21.31 duplication in an Italian family. Discussion: Clinical features and genetic data are reported, and compared with previously reported patients with 17q21.31 microduplication. A comparison of clinical manifestations between deletion and duplication syndromes of the chromosome regione is provided. Highlights: First report of a familiar transmission of 17q21.31 duplication syndrome. Description of the phenotype in proband and affected relatives. Further delineation of the clinical spectrum. Detailed description of neurobehavioral phenotype. First evidence of complete penetrance with variable expressivity in affected relatives.